IRON DEFICIENCY AND ‘SPORTS ANAEMIA’ IN YOUNG FEMALE ATHLETES - Kozicka, Julia; Mazur, Marcin; Wojtanowska, Ewa; Jachimczak, Ewa; Jaruga, Paulina; Grodkowska-Szukała, Karolina; Paczyna, Julia; Gąsiorowska, Vanessa; Suszczyńska, Aleksandra; Klimczyk, Hanna (International Journal of Innovative Technologies in Social Science, 2026)
Iron deficiency, including non-anaemic iron deficiency (NAID), is a common problem among young, menstruating female athletes, requiring precise differentiation from ‘athlete’s anaemia’, which is a physiological adaptive haemodilution. The aim of this narrative review was to summaries the mechanisms, prevalence, diagnostic principles, and clinical and performance-related consequences of these disorders. Epidemiological data indicate that hypoferritinaemia (ferritin ≤30 ng/mL) affects up to 47% of young female athletes, and 23.1% develop overt anaemia according to WHO criteria. The Pathomechanism of the negative iron balance is multifactorial and includes losses through sweat, gastrointestinal micro bleeding, mechanical haemolysis, and exercise-induced increases in interleukin-6 and hepcidin, which temporarily block intestinal iron absorption and recycling. It has also been shown that aerobic training is associated with a poorer haematological profile than anaerobic training. The consequences of NAID extend beyond reduced physical performance and fatigue, also including a decrease in bone mineral density and an increased risk of stress injuries to the lower limbs. In laboratory diagnostics, haemoglobin alone has been shown to have low sensitivity, which justifies routine measurement of ferritin (with the sports threshold raised to